Assessing the impact of bifacial solar photovoltaics on future power systems based on capacity-density-optimised power plant yield modelling - Keiner, Dominik; Walter, Lukas; Bogdanov, Dmitrii; Peters, Ian Marius; Breyer, Christian (Solar Energy, 2025)
Bifacial solar photovoltaic (PV) technology is currently taking over the solar PV module market, exceeding a 90% share in 2025. This important technology must be included in energy system modelling. This study provides a method for calculating the yield of monofacial and bifacial power plants in fixed-tilted, single-axis tracking, and east–west facing vertical setup. A novel method is introduced to maximise the capacity density of solar PV power plants without the need for detailed land cost for the most efficient use of the occupied area. The results indicate a 15–20% yield gain from single-axis tracking compared to fixed-tilted power plants, and a limited bifacial gain of up to 10% for most areas of the world. Higher bifacial gains are sporadically possible in specific conditions. Fixed-tilted systems show higher bifacial gains. Optimising tilt angles and row pitch would allow for 147 MW/km2 capacity density today, though on average 70–110 MW/km2 can be achieved for 20.2% module efficiency. The impact on the power system, studied in a free cost optimisation scenario and forcing vertical bifacial PV scenario, implying agrivoltaics, is not significant with a ± 10% change in total solar PV capacity, change in installed wind power of on average −10%, increase of installed battery capacity of on average 5%, and an on average changed levelised cost of electricity of −2% globally. Bifacial solar PV technology has been found to be beneficial but no game changer for future power systems; system improvements are widely possible underlining the important role of this technology.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Bifacial; Capacity density; Energy system modelling; Monofacial; Photovoltaics; Power plant